PENGARUH DANA DESA DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMISKINAN DI ACEH - Syarifah Annisa; Chenny Seftarita (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
Abstract Poverty is a problem faced by every country which must be done to overcome or reduce poverty. Village funds are funds distributed by the central government to regions through the APBD in an effort to increase poverty levels. This study aims to find out how village development funds and economic growth affect poverty in Aceh. In the study using secondary data with quantitative analysis methods in estimating panel data and the data used are poverty data, data on village funds and data on the growth rate of the GRDP of the Province of Aceh from 2015 to 2017. The results of this study show the variable village funds have a negative and significant effect on poverty, on the variable of economic growth has a negative but not significant effect on poverty in AcehKeywords: Village Funds, Poverty, Economic Growth, GRDP